PROLACTIN INDUCES MATURATION OF GLUCOSE SENSING MECHANISMS IN CULTURED NEONATAL RAT ISLETS - Boschero, A. C.; Crepaldi, S. C.; Carneiro, E. M.; Delattre, E.; ATWATER, I (Endocrine Soc, 1993)
The effects of PRL treatment on insulin content and secretion, and Rb-86 and Ca-45 fluxes from neonatal rat islets maintained in culture for 7-9 days were studied. PRL treatment enhanced islet insulin content by 40% and enhanced early insulin secretion evoked by 16.7 mm glucose. Insulin release stimulated by oxotremorine-M, a muscarinic agonist, in the presence of glucose (8.3 or 16.7 mm) was unchanged by PRL treatment. However, PRL treatment potentiated phorbol 12,13-dibutyrate-stimulated insulin secretion in the presence of the above glucose concentrations. PRL treatment potentiated the reduction in Rb-86 efflux induced by glucose or tolbutamide and enhanced the increase in Rb-86 efflux evoked by diazoxide. PRL treatment slightly potentiated the increment in Ca-45 uptake induced by high concentrations of K+, but failed to affect the increment evoked by 16.7 mm glucose. Since glucose-induced Ca-45 uptake was not affected by PRL, we suggest that the enhancement in first phase insulin secretion evoked by glucose in the PRL-treated islets occurs at a step in the secretory process that may involve protein kinase-C. These data further support observations that PRL treatment increases islet sensitivity to glucose.